Characterization of Rhizobacteria from field grown Genetically Modified (GM) and non-GM maizes - Bumunang,Emmanuel Wihkochombom (2014)
This study was done to examine the rhizobacteria from field grown Genetically Modified (GM) maize and its non-GM counterpart. Rhizospheric soil samples were collected at 30 days after sowing (DAS) and at post-harvest from two experimental fields in Gauteng, South Africa. Total rhizobacteria (cfu/g) in GM and non-GM soil samples was not significantly different across the different media 30 DAS and at post-harvest. Rhizobacterial isolates obtained were biochemically characterized using the analytical profile index. Species of Pseudomonas, Aeromonas, Sphingomonas, Burkholderia, Stenotrophomonas, Achromobacter, Ewingella and Bacillus were screened in vitro for plant growth promoting traits such as, ammonia production, catalase activity, indole acetic acid production, phosphate solubilisation, hydrogen cyanide production and antifungal activity. All the 32 rhizobacterial strains tested in this study were positive for catalase activity, ammonia production and IAA production; 90.6% were positive for phosphate solubilisation, 34.3% for indicate antifungal activity but none for hydrogen cyanide production. These findings contributed to the quest for potential biofertilizers and biocontrol agents for sustainable agriculture.